Disney's land : Walt Disney and the invention of the amusement park that changed the world - Snow, Richard, 1947- (Scribner, 2019)
"By the early 1950s Walt Disney's great achievements in animation were behind him, and he was increasingly bored by the two-dimensional film medium. He wanted to work in three, to build an entirely new sort of amusement park, one that relied more on cinematic techniques than on thrill rides, one from which all tawdriness had been purged. He achieved it, but just barely: he ran out of money, had to borrow against his life insurance, fell out with his studio, frightened his family, and endured much ridicule. What he built was far more influential than is generally understood-for one thing, Disneyland's Main Street sparked an architectural preservation movement that touched every American downtown-and remains controversial: many see it as a retreat from life itself. What is beyond argument is that Disneyland was something new, both in public entertainment, and in the way its "lands" managed to chime with how millions of Americans wanted to view their country-six hundred million Americans so far, and they just keep on coming. It reflects the park's uniqueness, but just as strongly that of the man who built it with a watchmaker's precision, an artist's conviction, and the desperate, high-hearted recklessness of a riverboat gambler"--